(untitled) (UNED Research Journal, 2017)
In India, the two spotted razor fish is not among the main commercially important fisheries but has food and ornamental value. We report the occurrence of Iniistius bimaculatus (Rüppell, 1829) in Digha based on a 199mm long specimen. This species was previously reported in India only from the south-eastern and western coasts. Morphometric and meristic measurements were taken and the specimen was deposited in ICAR-Central Institute of Fisheries Education, Kolkata Centre Museum.